2021
DOI: 10.3389/fnins.2021.645998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diagnostic Markers for Major Depressive Disorder Using Machine Learning Methods

Abstract: BackgroundMajor depressive disorder (MDD) is a global health challenge that impacts the quality of patients’ lives severely. The disorder can manifest in many forms with different combinations of symptoms, which makes its clinical diagnosis difficult. Robust biomarkers are greatly needed to improve diagnosis and to understand the etiology of the disease. The main purpose of this study was to create a predictive model for MDD diagnosis based on peripheral blood transcriptomes.Materials and MethodsWe collected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…He et al found that base on 4 autophagy-related signature have a good diagnostic performance in MDD (AUC = 0.779) [ 26 ]. By using machine learning methods, Zhao et al constructed the classifiers of SVM, RF, kNN, and NB, and AUC for SVM, RF, kNN, and NB was 0.84, 0.81, 0.73, and 0.83, suggesting that they have a good diagnostic performance [ 27 ]. In this study, we found the AUC for IRGs model was 0.861, suggesting that IRGs model is better than the prediction performan of two recently published model.…”
Section: Discussionmentioning
confidence: 99%
“…He et al found that base on 4 autophagy-related signature have a good diagnostic performance in MDD (AUC = 0.779) [ 26 ]. By using machine learning methods, Zhao et al constructed the classifiers of SVM, RF, kNN, and NB, and AUC for SVM, RF, kNN, and NB was 0.84, 0.81, 0.73, and 0.83, suggesting that they have a good diagnostic performance [ 27 ]. In this study, we found the AUC for IRGs model was 0.861, suggesting that IRGs model is better than the prediction performan of two recently published model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the vast feature space of -omics datasets, creating an accurate model through penalised regression is often not difficult, however finding the right features for further study to infer biological understanding is harder. In recent years, feature selection has become a popular method for novel biomarker discovery [ 35 , 36 , 37 , 38 , 39 , 40 ] and the application of the novel feature selection methods in this paper could accelerate the discovery of biomarkers in many fields.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Zhao et al compared different machine learning approaches using the same data set which also used by us. It was found that compared with other methods, such as SVM, RF, kNN, NB, SVM could distinguish MDD from healthy controls more accurately ( Zhao et al, 2021 ). Overall, compared with previous studies, our model evaluation provides new ideas for the application of peripheral blood in aiding diagnostic machine learning.…”
Section: Discussionmentioning
confidence: 99%